On the origins and evolution of qualia: An experience-space perspective - Lacalli, Thurston (Frontiers in Systems Neuroscience, 2022)
This paper elaborates on a proposal for mapping a configuration space for selector circuits (SCs), defined as the subset of neural correlates of consciousness (NCCs) responsible for evoking particular qualia, to its experiential counterpart, E-space, as part of an investigation into the nature of conscious experience as it first emerged in evolution. The dimensionality of E-space, meaning the degrees of freedom required to specify the properties of related sets of qualia, is at least two, but the utility of E-space as a hypothetical construct is much enhanced by assuming it is a large dimensional space, with at least several times as many dimensions as there are categories of qualia to occupy them. Phenomenal consciousness can then be represented as having originated as one or more multidimensional ur-experiences that combined multiple forms of experience together. Taking this as a starting point, questions concerning evolutionary sequence can be addressed, including how the quale best suited to a given sensory modality would have been extracted by evolution from a larger set of possibilities, a process referred to here as dimensional sorting, and how phenomenal consciousness would have been experienced in its earliest manifestations. There is a further question as to whether the E-space formulation is meaningful in analytical terms or simply a descriptive device in graphical form, but in either case it provides a more systematic way of thinking about early stages in the evolution of consciousness than relying on narrative and conjecture alone.